The mediating role of IPA in attracting and retaining FDI in developing countries: Insights from Ghana and Nigeria - Samuel Ebie (Proceedings of the 2019 Conference Academy of International Business Africa Conference, 2019)
The international business scholarship has acknowledged the role of investment promotion activities as significant policy instruments in attracting inward investments to host economies. Notwithstanding, research specifically examining the role of investment promotion agencies (IPAs) in attracting and retaining inward FDI has been the subject of rather dated and limited studies with mixed and inconclusive findings. This body of scholarship has also mainly examined the direct impact of IPAs. The purpose of this study therefore is to examine the moderating role of IPAs in attracting and retaining inward FDI in two developing West African countries: Ghana and Nigeria.